Promoting "Zest for Life": A Systematic Literature Review of Resiliency Factors to Prevent Youth Suicide. (4th March 2021) - Shahram, Sana Z.; Smith, Michelle L.; Ben‐David, Shelly; Feddersen, Melissa; Kemp, Thomas E.; Plamondon, Katrina
Abstract : Suicide is a leading cause of death among youth globally. In this critical interpretive synthesis, we examined literature on resiliency factors and suicidality. Systematic searches identified 474 articles, 37 of which were included. Results revealed internal (positive self‐appraisal, zest for life, personal traits, and coping skills) and external factors (social support system and inclusive environments) contribute to resilience among youth, with age, sex and gender, and Indigenous identity as important intersecting considerations. Findings validated fostering resilience as primary suicide prevention among youth, with little explanation for how these factors may work to protect youth from suicidality. Continued research in this area requires a focus on how to promote resilience at the community and systems levels.